In search of the official definition of nursing - Henderson, Virginia (The nature of nursing : a definition and its implications for practice, research, and education, 1966)
vii, 84 p. : 24 cm; "Contents grew out of a Clare Dennison memorial lecture at the University of Rochester School of Nursing ... 1964. A condensed version was published in The American journal of nursing in August, 1964."; DON306/2001; Bibliographical references included in "Library tools for nursing" (p. 70-79) Bibliography: p. 80-84; 2001 08 30
Keywords: Nursing -- Philosophy